Socio-demographic, maternal, and infant characteristics associated with pacifier use among six-months old infants in Clark County, Nevada - Saniatan, Kaelia Lynn; Neupane, Smriti; Cross, Chad; Buccini, Gabriela (PLOS ONE, 2023)
Background Pacifier use can interfere with nurturing care practices such as breastfeeding, soothing, and sleeping. Due to contradicting beliefs, recommendations, and the high frequency of pacifier use, understanding its associations may support shaping equitable public health recommendations. This study explored the socio-demographic, maternal, and infant characteristics associated with pacifier use among six-months old infants in Clark County, Nevada. Method Cross-sectional survey was conducted in 2021 with a sample of mothers (n = 276) of infants under six months old in Clark County, Nevada. Participants were recruited through advertisements in birth, lactation, pediatric care centers, and social media. We used binomial and multinomial logistic models to assess the association between pacifier use and the age of pacifier introduction, respectively, with household, maternal, infant, healthcare characteristics, and feeding and sleeping practices. Results More than half of the participants offered pacifiers (60.5%). Pacifier use was higher among low-income households (OR (95% CI) 2.06 (0.99–4.27)), mothers who identified as non-Hispanic (OR (95% CI) 2.09 (1.22–3.59)), non-first-time mothers (OR (95% CI) 2.09 (1.11–3.05)), and bottle-feeding infants (OR (95% CI) 2.76 (1.35–5.65)). Compared to those who did not introduce a pacifier, non-Hispanic mothers (RRR (95% CI) 2.34 (1.30–4.21)) and bottle-fed infants (RRR (95% CI) 2.71 (1.29–5.69)) had a higher risk of introducing pacifier within two weeks. Likewise, infants living in food insecure households (RRR (95% CI) 2.53 (0.97–6.58)) and mothers who have more than one child (RRR (95% CI) 2.44 (1.11–5.34)) had a higher risk of introducing a pacifier after two weeks. Conclusion Pacifier use is independently associated with maternal income, ethnicity, parity, and bottle feeding among six-month-old infants living in Clark County, Nevada. Household food insecurity increased the relative risk of introducing a pacifier after two weeks. Qualitative research on pacifier use among families with diverse ethnic/racial backgrounds is needed to improve equitable interventions.